Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

This question already has an answer here:

How can I find the closed form of

a) 1+3+5+...+(2n+1)
b) 1^2 + 2^2 + ... + n^2

using induction?

I'm new to this site, and I've thought about using the series 1 + 2 + 3 +...+ n = n(n+1)/2 to help me out But isn't that technically using prior knowledge and hence invalid? Am I on the right track? Thanks.

share|improve this question

marked as duplicate by O.L., Andrey Rekalo, Davide Giraudo, Danny Cheuk, Daniel Rust Jul 12 '13 at 14:25

This question has been asked before and already has an answer. If those answers do not fully address your question, please ask a new question.

    
    
Well, you don't try to find a closed form expression using induction, you prove whatever you come up with is correct by using induction. Using prior knowledge to help you discover a potential formula isn't invalid, it's to be encouraged! –  stochasm Jul 7 '13 at 15:16

1 Answer 1

$a):$ Clearly it is an Arithmetic Series

So, the sum up to $n$th term is $=\frac n2\{2\cdot1+(n-1)2\}=n^2$

Let $P(n):\sum_{1\le r\le n}(2r-1)=n^2$

$P(1):\sum_{1\le r\le 1}(2r-1)=1$ which is $=1^2$ so $P(n)$ is true for $n=1$

Let $P(n)$ is true for $n=m$

So, $\sum_{1\le r\le m}(2r-1)=m^2$

$P(m+1): \sum_{1\le r\le m+1}(2r-1)=\sum_{1\le r\le m}(2r-1)+2m+1=m^2+2m+1=(m+1)^2$

So, $P(m+1)$ will be true if $P(m)$ is true.

But we have already shown $P(n)$ is true for $n=1$

So, by induction we can prove that $P(n)$ is true for all positive integer $n$

$b):$

HINT:

We know, $(r+1)^3-r^3=3r^2+3r+1$

Putting $r=1,2,\cdots,n-1,n$ and adding we get $(n+1)^3-1=3\sum_{1\le r\le n}r^2+3\sum_{1\le r\le n}r+\sum_{1\le r\le n}1$

Now, you know $\sum_{1\le r\le n}r=\frac{n(n+1)}2$ and $\sum_{1\le r\le n}1=n$

On simplification $\sum_{1\le r\le n}r^2=\frac{n(n+1)(2n+1)}6$

Can you use similar induction approach here?

share|improve this answer
    
Right, but that's using S = n/2(a_1+a_n) formula, where a_n = a_1+(n-1)*d. How do I proceed using induction? –  Anonymous Jul 7 '13 at 14:45
    
@AbhishekMallela, induction needs a statement, right? –  lab bhattacharjee Jul 7 '13 at 14:46
    
Not according to the problem statement in my textbook! –  Anonymous Jul 7 '13 at 14:48
    
Thank you very much! –  Anonymous Jul 7 '13 at 14:51
    
@AbhishekMallela, my pleasure. –  lab bhattacharjee Jul 7 '13 at 14:58

Not the answer you're looking for? Browse other questions tagged or ask your own question.